Music Cultural Knowledge Transfer of Sea Gypsies Group in Satun Province - Ungpho, Rewadee (Journal of Cultural Approach, 2019)
The objective of this research was to investigate the cultural knowledge transfer of the Sea Gypsies ethnic group, Urak Lawoi, in Satun province. This qualitative research employed an ethnomusicological method. The population includes 5 Urak Lawoi musicians and performers in Bulon Archipelago and Lipe Island, as the main group. Informants of an overall picture were 10 community leaders and people in both islands as a secondary group who provided both direct and indirect information. The qualitative data analysis was undertaken by a content processing and information comparison. The results revealed that the knowledge capital on musical culture of Urak Lawoi in Satun existed in people of the middle age or over in both islands, and their cultural knowledge was transferred mainly to school age youth. Initially, the cultural capital of Bulon Archipelago included music and dance, while only dance existed in Lipe. The cultural capital was transferred in 2 ways, i.e. within island and between islands. The knowledge and practice of musical culture had developed and changed by the environmental situation and social factors, resulting in 2 types of music and performance which included performance for the community in an original cultural way, and performance to serve the need of tourists.